Avaliação da ação cicatricial e repelente de Carapa guianensis e Caesalpinia ferrea Mart. - Fernandes, Ciciane Pereira Marten (2013)
The aim was to evaluate the healing of open cutaneous wounds of Wistar rats treated with Carapa guianensis (andiroba) and Caesalpinia ferrea Mart. (Jucá) and their repellent action against flies of the Calliphoridae family. It were studied 160 Wistar rats with open wounds in the back that were treated daily with Carapa guianensis at concentrations of 20% (A20) and 50% (A50), Caesalpinia ferrea Mart. concentrations at 20% (J20) and 50% (J50) and Vaseline (control group). Clinical, histological and morphometric studies were carried out after four, seven, 14 and 21 days of treatment, as well as a tensiometric study after 21 days. In order to study the repellency, W.O.T traps (Wind Oriented Trap) containing deteriorated bovine liver and cream with the herbal medicine Carapa guianensis and Caesalpinia ferrea Mart. at concentrations of 20% and 50% were used to catch flies. Clinically, after four days of treatment, the wounds of the control group presented exudate, differing statistically from the other groups (p=0.0065). In the morphometric study, J50 and J20 groups had higher average area (p=0.0001) after seven days of treatment, whereas after 14 days, the wounds of the control group had higher average area (p=0.0000) compared with the other groups. In the histopathological study, the differences between groups were seen after four days of treatment, with the A20 group showing a greater number of wounds in the proliferative phase (p=0.0000). In the tensiometric study, the control group showed better results (3.52MPa) in tension when compared to other groups (p=0.0055). In the repellency study, the traps containing J50 (p<= 0.010) and D20 (p<= 0.010) showed a higher repellency 97% and 100%, respectively, followed by the A50 group (p<= 0.010) with 93.4% and the A20 group with 56.5%. The results led to the following conclusions: Carapa guianensis at a concentration of 20% accelerates the phases of the healing process in the first days after tissue injury, whereas Carapa guianensis at 50% and Caesalpinia ferrea Mart. at concentrations of 20% and 50% do not show satisfactory results as a cicatrizant. As repellent action, Caesalpinia ferrea Mart. at concentrations of 50% and 20% and Carapa guianensis at 50% have repellent effect against Chrysomya albiceps, Chrysomya megacephala, Lucilia cuprina, Lucilia eximia, Lucilia sericata and Sarconesia chlorogaster flies, species of the Calliphoridae family, while the Carapa guianensis at 20% has less repellent action.